The Influence of Reading Habit on The Science Learning Outcomes of Class VII Even Semester Students at MTS Negeri 2 Surakarta - Febrian, Anggi Setyani; Kusumadani, Annur Indra (Journal of Biology Learning, 2024)
Literacy skills especially reading in Indonesia are still low. To improve reading literacy, literacy training can be done before learning. Literacy reading habits can be done with 15 minutes of reading material before learning begins. The aim of this research is to determine the effect of reading habits on the science learning outcomes of class VII students in the even semester at MTs Negeri 2 Surakarta for the 2023/2024 academic year. This research method is a quantitative descriptive method. The type of research is quasi-experimental research with purposive sampling technique. The data collection techniques used were observation, interviews, tests, questionnaires and documentation. Based on the results of data analysis that has been carried out using the linearity test, it gets a significant value of 0.734 > 0.05, so there is a linear relationship between the two research variables and the results of the Mann Whitney test, a significant value of 0.0007 < 0.05, meaning there is a difference in the average of the samples. second. So it can be concluded that there is a significant influence between the habit of reading on the science learning outcomes of class VII students at MTs. Negeri 2 Surakarta Academic Year 2023/2024